The ionising cluster of 30 Doradus : IV. Stellar kinematics - Bosch, Guillermo Luis (2001)
On the basis of multislit spectroscopy of 180 stars in the ionising cluster of 30 Doradus we present reliable radial velocities for 55 stars. We calculate a radial velocity dispersion of ∼35 km s-1 for the cluster and we analyse the possible influence of spectroscopic binaries in this rather large velocity dispersion. We use numerical simulations to show that the observations are consistent with the hypothesis that all the stars in the cluster are binaries, and the total mass of the cluster is ∼5 × 105 M⊙. A simple test shows only marginal evidence for dynamical mass segregation which if present is most likely not due to dynamical relaxation.